2021
DOI: 10.3390/agriculture11111050
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Attitude towards Sustainable Food Consumption during the COVID-19 Pandemic in Romania

Abstract: The COVID-19 pandemic affected consumers’ behavior worldwide. This paper aims to analyze consumers’ sustainable food behavior during the COVID-19 pandemic. The research was based on an online survey during May–October 2020 among 859 Romanian consumers. Principal component analysis and cluster analysis were employed to group the consumers based on their behavior. Furthermore, the binary-logistic regression was used to identify the socio-demographic profile of the identified groups. Based on the cluster analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“… Young people started food management practices during the pandemic Cosgrove et al (2021) ; Everitt et al (2021) ; Hassen et al (2021a) ; Liu et al (2021) ; Muresan et al (2021) ; Principato et al (2020) ; Qian et al (2020) ; Scacchi et al (2021) ; Vittuari et al (2021) Education Higher academic levels lead to less food waste usually. Hassen et al (2020); Hassen et al (2021a) ; Muresan et al (2021) Employment Status Employment status influences lifestyle (e.g., dietary habits and daily schedules) Unemployment leads to food waste reduction Amicarelli et al (2021) ; Berjan et al (2021) ; Qian et al (2020) ; Scacchi et al (2021) ; Scharadin et al (2021) ; Vidal-Mones et al (2021) Income Loss of income leads to food waste reduction Higher incomes lead to higher food waste. Bender et al (2021) ; Hassen et al (2021a) ; Hassen et al (2021b) ; Jribi et al (2020) ; Özbük et al (2021) ; Qian et al (2020) ; Scharadin et al (2021) ; Vittuari et al (2021) Time Availability Working from home More time to develop cooking skills.…”
Section: Thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“… Young people started food management practices during the pandemic Cosgrove et al (2021) ; Everitt et al (2021) ; Hassen et al (2021a) ; Liu et al (2021) ; Muresan et al (2021) ; Principato et al (2020) ; Qian et al (2020) ; Scacchi et al (2021) ; Vittuari et al (2021) Education Higher academic levels lead to less food waste usually. Hassen et al (2020); Hassen et al (2021a) ; Muresan et al (2021) Employment Status Employment status influences lifestyle (e.g., dietary habits and daily schedules) Unemployment leads to food waste reduction Amicarelli et al (2021) ; Berjan et al (2021) ; Qian et al (2020) ; Scacchi et al (2021) ; Scharadin et al (2021) ; Vidal-Mones et al (2021) Income Loss of income leads to food waste reduction Higher incomes lead to higher food waste. Bender et al (2021) ; Hassen et al (2021a) ; Hassen et al (2021b) ; Jribi et al (2020) ; Özbük et al (2021) ; Qian et al (2020) ; Scharadin et al (2021) ; Vittuari et al (2021) Time Availability Working from home More time to develop cooking skills.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Education is another factor that may influence household food waste generation (Hassen et al, 2020). Although its relationship with food waste reduction during the COVID-19 pandemic has received less attention, three studies have reported its impact (Hassen et al, 2020, 2021a ; Muresan et al, 2021 ). In a study in Romania, Muresan et al (2021) found that people with higher education degrees were more engaged in sustainable behaviours and food waste reduction.…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that consumers’ attitudes and behaviors toward production practices and locations may vary even depending on the nationality of the consumer, that product labeling works differently depending on the type of product and the consumers’ reaction to information is temporary, and that education has no effect on students’ risk perception ( 27 , 28 ). However, in the context of certain factors affecting the global economy such as the current COVID-19 pandemic, age, and level of education are key elements in changing consumer behavior, especially for consumers’ attitudes toward sustainable food choices ( 29 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, evidence shows that the COVID-19 pandemic might affect the dietary structure and consumer behavior [36,37]. For example, consumers may prefer healthy diets [38,39], the demand for online food delivery may increase [40,41], panic buying may occur [42], and sustainable food consumption may be promoted [43][44][45].…”
Section: Introductionmentioning
confidence: 99%